Social Innovation of Livablehome as a City Government Policy in Social Development in Prabumulih City - Adi Suhendra (Inovbook Publications, 2022)
This research is about innovation or policy of a region in the context of poverty alleviation. This research is relevant and interesting to discuss because with the creation of this innovation, the Prabumulih City Government received a MURI Record certificate for the Poverty Alleviation Program (Development) of 10 livable houses/month without using APBD, APBN, and CSR funds in 2016. This innovation is of course can be a motivation for other regions that have similar problems, so as to minimize the occurrence of poverty.The population in this study is an area that has created innovations in the context of poverty alleviation. While the sample in this study is a livable house as a policy of the Prabumulih City Government to Empower the Participation of Civil Servants and Non Civil Servants in Poverty Alleviation of the Prabumulih City Community. The results of this study indicate that the innovations created by Prabumulih Regency have succeeded in achieving the goals that have been set, where the construction of habitable houses has helped many poor people to have houses that meet health standards so that they become comfortable housing for regional innovation programs with zakat/ infaq of employees within the Prabumulih City Government.